영아기 자녀를 둔 어머니의 양육방식 및 양육스트레스가 기본생활습관에 미치는 영향 - 한영숙(Young-Suk Han) (한국콘텐츠학회 논문지, 20(5), 2020)
The purpose of the study was to investigate the effects of the mother's parenting style and parenting stress on infant's basic living habits. The subjects for the study were 155 infants and their mothers. The collected data was analyzed using descriptive statistics, correlation analysis, and a multiple regression model technique. The results of the of the correlation analysis showed some significant positive correlations between the mother's parenting style and the infant's basic living habits. In addition, the mother's parenting stress showed the effects of a significant negative correlation with the infant's sleeping habit and eating habit, a sub-factor of the basic living habits. The importance of the mother's parenting style and parenting stress are discussed in terms of the relation to the developing infant's basic living habits. 본 연구는 어머니의 양육방식 및 양육스트레스가 영아의 기본생활습관에 미치는 영향력을 분석하는 데 그 목적이 있다. 연구대상은 영아와 그들의 부모 155명이다. 기술통계, 상관관계분석, 중다회귀분석으로 자료를 분석하였다. 그 결과 어머니의 온정·격려, 한계설정 양육방식은 기본생활습관에 긍정적인 영향을 미치고 있지만 과보호·허용, 거부·방임 양육방식은 기본생활습관 형성에 부정적인 영향을 미치는 것으로 나타났다. 또한 어머니의 양육스트레스는 수면습관과 식습관에 부정적인 영향을 미치는 것으로 나타났다. 이에 본 연구는 어머니의 양육변인인 양육방식과 양육스트레스가 영아기 기본생활습관에 미치는 영향을 분석하여 영아기 사회화 및 사회적 발달과 관련된 기초자료를 제시하는데 의의를 갖는다.